Multiple Myeloma Involving Left Hemicranium - Jutty Parthiban; B. Udaykumar; Sudeendra Reddy Peddireddy; Balasubramaniam Prakash; Vighnesh Kandha Kumar (Indian Journal of Neurosurgery)
Multiple myeloma (MM) is a malignant neoplasm of bone marrow affecting plasma cells. It is commonly seen as multiple punched-out lesions in the skull bone as a characteristic feature. Its presentation as hemicranial involvement with intracranial extension is rare. A 46-year-old male presented with left side scalp swelling, prominent over parietal region. X-ray showed multiple punched out lesions involving left hemicranium. CT and MRI brain showed intracranial extension of lesion without brain parenchyma invasion. He was treated with biopsy of lesion followed by chemotherapy.